CONTRIBUTION TO OPTIMIZING THE PERFORMANCES OF ANAEROBIC REACTOR - Abdelilah, Abid; Eddine, Jellal Jamal (European Scientific Journal, ESJ, 2014)
The Integrated System: Anaeorobic Reactor – High Rate Algal Pond (AR-HRAP) is new approach combining high-rate anaerobic/aerobic units for wastewater treatment. In this combination, the anaerobic reactor plays a crucial role. Thus, control of hydrodynamics will both improve the design of such a structure and optimize its performance. According to several researchers, the hydrodynamic flow modeling is as important as the kinetic modeling of reactions. This study aims to elaborate flow simulations for different residence times (1.5 d, 2 d, 3 d) in the anaerobic reactor, using software FLUENT. This study has allowed us to have interesting results regarding hydrodynamic of anaerobic reactor.